Unusual structural characteristics of the Mycobacterium tuberculosis pentapeptide repeat protein MfpA. Issue 3 (2010) - Khrapunov, S.; Cheng, H.; Hegde, S.; Blanchard, J.; Brenowitz, M.
Abstract : The solution structure and refolding of the Mycobacterium tuberculosis pentapeptide repeat protein MfpA was explored by fluorescence and circular dichroism spectroscopy. Our results show that MfpA exists in two stable structural forms which exclusively favor dimer or oligomer formation. The structural malleability of MfpA may provide a novel target for drug discovery.